Adverse Childhood Experiences are Associated with High-Intensity Binge Drinking Behavior in Adulthood and Mediated by Psychiatric Disorders. (2nd January 2020) - Jung, Jeesun; Rosoff, Daniel B; Muench, Christine; Luo, Audrey; Longley, Martha; Lee, Jisoo; Charlet, Katrin; Lohoff, Falk W
Abstract: Aim: High-intensity binge drinking (HIBD), defined as two or more times the gender-specific binge threshold, is rapidly increasing in the USA; however, the underlying contributing factors are poorly understood. This study investigated the relationship of adverse childhood experiences (ACEs) and HIBD. Methods: Two independent, cross-sectional samples were analysed: (a) past 12-month drinkers in the National Epidemiological Survey on Alcohol and Related Conditions-III (NESARC-III; n  = 25, 552) and (b) the National Institute on Alcohol Abuse and Alcoholism (NIAAA) clinical sample ( n  = 1303). Multinomial logistic regressions were utilized to estimate adjusted odds ratios (AORs) of ACEs on HIBD. Mediation analysis was performed to examine the relationship between the past 12-month psychiatric disorders, ACEs, and HIBD. Results: In the NESARC-III sample, prevalence of ACEs increased across all binge levels with the highest prevalence in extreme HIBD; ACEs were associated with higher odds for HIBD (level II, odds ratio (OR) = 1.2–1.4; P  = 0.03–0.001; level III, OR = 1.3–1.9; P  < 0.001). Prevalence of DSM-5 diagnoses also increased across all binge levels. Substance use disorders (SUD), mood, personality and post-traumatic stress disorders (PTSD) conferred the highest odds with extreme HIBD (SUD: OR = 21.32; mood: 1.73; personality: 2.84; PTSD: 1.97; all Ps  < 0.001). Mediation analyses showed that the association between ACEs and HIBD was fully mediated through SUD (proportion mediated: 70–90%) and partially through other psychiatric disorders (20–80%). In the NIAAA sample, ACEs were 2–5 times more prevalent in extreme HIBD with higher odds (ORs = 3–8, P  < 0.001) compared with non-bingers. Conclusion: ACEs were associated with significantly increased odds of HIBD and the relationship may be mediated by psychiatric disorders. Abstract : ACEs and comorbid psychiatric disorders are significant risk factors for HIBD, defined as two or more times the gender-specific binge threshold. Psychiatric disorders play a full or partial mediating role in the relationship between ACEs and HIBD.